2021
DOI: 10.1007/s13167-021-00243-4
|View full text |Cite
|
Sign up to set email alerts
|

Positive influence of gut microbiota on the effects of Korean red ginseng in metabolic syndrome: a randomized, double-blind, placebo-controlled clinical trial

Abstract: Background Ginseng, a traditional herbal medicine, has been used for thousands of years to treat various diseases including metabolic syndrome (MS). However, the underlying mechanism(s) of such beneficial actions of ginseng against MS is poorly understood. Emerging evidence indicates a close association of the host gut microbiota with MS. The present study was conducted to examine, whether the beneficial effects of Korean red ginseng (KRG) against MS could be influenced by gut microbial population and whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 134 publications
(190 reference statements)
2
13
0
Order By: Relevance
“…The results showed that all the samples clustered into 1 of 3 enterotypes. The Bacteroides and Prevotella enterotypes were identical to those reported earlier in other diseases (27)(28)(29) and the 3rd enterotype was distinguished by high levels of Alistipes and Eubacterium, which have never been reported, may be unique to patients with STC, and were different from other types of diseases. Some strong correlations occur between host properties and particular functions at the gene or module level (a module is a part of a pathway that is functionally tightly interconnected); we also attempted to identify bacterial biomarkers that may help in the diagnosis of STC by generating 10 different metagenomic shotgun markers.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results showed that all the samples clustered into 1 of 3 enterotypes. The Bacteroides and Prevotella enterotypes were identical to those reported earlier in other diseases (27)(28)(29) and the 3rd enterotype was distinguished by high levels of Alistipes and Eubacterium, which have never been reported, may be unique to patients with STC, and were different from other types of diseases. Some strong correlations occur between host properties and particular functions at the gene or module level (a module is a part of a pathway that is functionally tightly interconnected); we also attempted to identify bacterial biomarkers that may help in the diagnosis of STC by generating 10 different metagenomic shotgun markers.…”
Section: Discussionsupporting
confidence: 79%
“…The results showed that all the samples clustered into 1 of 3 enterotypes. The Bacteroides and Prevotella enterotypes were identical to those reported earlier in other diseases ( 27 29 ) and the 3rd enterotype was distinguished by high levels of Alistipes and Eubacterium, which have never been reported, may be unique to patients with STC, and were different from other types of diseases.…”
Section: Discussionsupporting
confidence: 78%
“…Tumor-associated microbes could predict to the occurrence of cancer. On the other hand, microbes enriched in tumor pose unexpected effects on the therapeutic effect of different cancer treatments (including radiotherapy, chemotherapy, and especially immunotherapy) [23,24]. Our previous 16S rRNA sequencing analysis suggested that there were distinct microbial signatures in ovarian cancer tissue as compared to the normal fallopian tube tissue [4].…”
Section: Discussionmentioning
confidence: 98%
“…In obesity animal models, Firmicutes, Bacteroides, Lactobacillus , and Helicobacter may be potential targets for ginseng in the treatment of obesity ( Table 1 ). Meanwhile, relative studies have found ginseng could reduce the body weight, blood lipid, blood glucose, and inflammatory level, as well as can significantly improve the structure of gut microbiota in obese patients ( Table 2 ) ( Song et al., 2014 ; Seong et al., 2021 ).…”
Section: Ginseng Treats Various Diseases By Regulating Gut Microbiotamentioning
confidence: 99%
“…Besides these ginsenosides, the combination of red ginseng, Aronia, Shiitake mushroom, and Nattokinase and Buzhong Tongluo decoction including Astragalus membranaceus , Dioscorea hemsleyi , Salvia miltiorrhiza , Scrophularia ningpoensis , Ophiopogon japonicus , Panax ginseng , Fritillariae cirrhosae , and Whitmania pigra Whitman have been proved to be able to up-regulate Bacteroides, Lactobacillus, Akkermansia probiotics, reduce the abundance of bacteria causing hyperglycemia, such as Helicobacter , Flavonifractor , and reduce the ratio of Firmicutes and Bacteroidetes , thus play their hypoglycemic effects ( Yang et al., 2018 ; Zheng et al., 2020 ). In another disorder, metabolic syndrome, the powder from Korean red ginseng (KRG) has a good therapeutic effect, and its mechanism might be related to the improvement of the disorder of lipid metabolism (the reductions of TC and low-density lipoprotein, LDL) by increasing the relative abundance of Bacteroides and reducing the relative abundance of Firmicutes and Proteobacteria ( Seong et al., 2021 ). Most studies show that ginseng can correct the abnormal metabolic level in the body by reversing the ratio of Firmicutes and Bacteroidetes .…”
Section: Ginseng Treats Various Diseases By Regulating Gut Microbiotamentioning
confidence: 99%